Bilateral mantle cell lymphoma of the ciliary body that responded to a combined local radiotherapy and chemotherapy regimen: a case report - Minghang Pei (BMC Cancer, 2019)
Abstract Background Mantle cell lymphoma (MCL) is a rare, aggressive B-cell non-Hodgkin lymphoma (NHL) that often affects men over the age of 60. Systemic metastasis of MCL to eyes is rare and intraocular involvement is even rarer, which usually affects the choroid and iris. To the best of our knowledge, ciliary body metastasis of systemic MCL has not been reported. Case presentation A 59-year-old Han Chinese male with past-history of systemic MCL complained of redness, pain and blurred vision in the left eye. Ocular examination revealed a normal appearance in the right eye, and conjunctival injection, pseudohypopyon and anterior protrusion of peripheral iris in the left eye, all of which were unresponsive to corticosteroid treatments. Ultrasound biomicroscopy (UBM) and B-scan were then performed which detected ciliary body masses in both eyes with no vitreous and retino-choroidal anomalies. Combined liquid-based cytology tests and gene rearrangement assays of the aqueous humor specimen confirmed this to be a B-cell malignancy. Then both eyes were treated with external beam irradiation (40 Gy, delivered evenly in twenty fractions) over a course of one month. Additionally, the left eye received intravitreal methotrexate (MTX) (weekly for the first month, every two weeks for the second month, and monthly thereafter) over a course of twelve months. This therapy eventually led to complete remission of all symptoms in one month and disappearance of the ciliary body masses in twelve months. Conclusion Here we first reported a case of bilateral ciliary body MCL infiltration which was diagnosed by combined liguid-based cytology and gene rearrangement of aqueous humor cells. UBM may serve as a valuable tool in the diagnosis and serial assessments of anterior segment tumors.